Reduced reproductive fitness of an endemic insular juniper population: An eco-genetic mediation hypothesis. (June 2016) - García, C.; Rumeu, B.; González-Pérez, M.A.; Nogales, M.
Abstract: The mutual reinforcement of multiple drivers of global change erodes ecosystem services and accelerates plant population decline worldwide. This is particularly the case for island ecosystems where anthropogenic activity has imperilled insular floras for centuries. Different hypotheses have put forward the combined effects of environmental shifts and genetic factors in driving fecundity decline in threatened populations. In this study, we combined population genetic tools and structural equation models to test the eco-genetic mediation hypothesis, that the environmental conditions influence genetic variation, which in turn affects plant fitness. Our study species is Juniperus cedrus, an endangered juniper species endemic to the Canary Islands. Juniper woodlands have been depleted since the arrival of human inhabitants confined extant populations to marginal lands. More recently, long-distance dispersers have been extirpated from the study area, potentially eliminating connectivity among fragmented populations. We expected strong intrapopulation subdivision and high levels of inbreeding and kinship that should negatively affect individual fitness. We found evidence of population subdivision into several mating neighbourhoods ( K  = 13), some of them highly inbred. However, contrary to our expectations, neither inbreeding nor mean kinship mediated a population response to environmental factors. Our results suggest three remedial actions to reverse the declining demographic trends: (i) re-establish native vegetation to ameliorate local environmental conditions; (ii) restore dispersal services to increase connectivity; and (iii) monitor fitness decline to identify lagged effects associated with deforestation. Overall, this study shows that structural equation models combined with population genetic techniques are suitable tools to identify high-order effects among multiple drivers of global change that underlie forest decline. Highlights: Reinforcement among drivers of global change accelerates population decline worldwide. An overall assessment of the effects of inbreeding on fecundity is urgently needed. SEMs can unfold high-order effects among eco-genetic factors underlying forest decline. Inbreeding did not mediate fitness decline in response to environmental conditions. Suboptimal environment impacted population fitness.